Non-traditional Security Threat in South Asia with Particular Orientation to IDP’s in Pakistan - Umbreen Javaid; Izzat Raazia (Journal of Political Studies, 2015)
In international relations, the idea of human security is a specific approach to security that is relating to human rights and governance. Academically and politically, the recent shift of attention from security to human security is a matter of concern. In traditional practices of security, military intercessions are the prioritization that is unsuccessful in responding the most pressing threats to individual security adequately, all over the world. The traditional security threats have served to further individual security challenges. Internal displacement has become a fact of life in South Asia that is a hall mark of conflict ridden regions of the world. Minority conflicts, religious and ethnic rifts, state repression, demands for sovereignty, famines, floods, terrorism, lack of development projects and IDPs crisis, all have added to the challenge of already aggravated human security conditions in South Asia. Pakistan, since long, has been facing IDPs crisis that is a challenge to human security, a sphere of security and it has become difficult to fully cope the issue by the leadership of Pakistan. As the repatriation of internally displaced persons and reconstruction of their areas after 2009 military offensive of Swat has been completed in the near past, Pakistan military resolved to flush out all terrorist outfits and initiated the military operation ‘Zarb-e-Azb’ in 2014, in North Waziristan Agency. In the aftermath of present operation, Pakistan is faced with a large displacement crisis, with almost one million people. The paper examines the phenomenon of internal displacement as a non-traditional security issue that poses a serious threat to the regional security of south Asia in general and to the internal security of Pakistan in particular.